2003
DOI: 10.2165/00003495-200363030-00003
|View full text |Cite
|
Sign up to set email alerts
|

Management of Chronic Inflammatory Demyelinating Polyradiculoneuropathy

Abstract: This review briefly describes current concepts concerning the nosological status, pathogenesis and management of chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). CIDP is an uncommon variable disorder of unknown but probably autoimmune aetiology. The commonest form of CIDP causes more or less symmetrical progressive or relapsing weakness affecting proximal and distal muscles. Against this background the review describes the short-term responses to corticosteroids, intravenous immunoglobulin (IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 104 publications
0
11
0
Order By: Relevance
“…There is a regrettable lack of information from controlled trials about the efficacy of immunosuppressive drugs. Responses to several drugs, particularly cyclosporine and cyclophosphamide, have been reported in observational studies ( Mahattanakul et al, 1996 ; Good et al, 1998 ; Hughes, 2003 ) . We have seen improvements in strength with methotrexate in seven of 10 patients ( Fialho et al, 2006 ) .…”
Section: Treatment Responsementioning
confidence: 99%
See 1 more Smart Citation
“…There is a regrettable lack of information from controlled trials about the efficacy of immunosuppressive drugs. Responses to several drugs, particularly cyclosporine and cyclophosphamide, have been reported in observational studies ( Mahattanakul et al, 1996 ; Good et al, 1998 ; Hughes, 2003 ) . We have seen improvements in strength with methotrexate in seven of 10 patients ( Fialho et al, 2006 ) .…”
Section: Treatment Responsementioning
confidence: 99%
“…In doing so, we have focused on the typical symmetrical sensory and motor core syndrome ( Hughes et al, 2005 ) and taken into account other recent reviews of the same topic ( Kieseier et al, 2004 ; Rezania et al, 2004 ) , presenting the evidence for each of the main proposals regarding etiology. Treatment of CIDP with immunomodulatory agents is only beneficial in two‐thirds of patients, and even in these the treatment response is often unsatisfactory ( Donofrio, 2003 ; Hughes, 2003 ) . A better understanding of the disease mechanisms should guide the design of better treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have shown that administration of IFN-a is effective for patients with CIDP that was refractory to conventional therapies. 2 We speculate that IFN-a might trigger a pathological autoimmune reaction, such as molecular mimicry, in some immunologically-predisposed patients, while suppressing pathological autoimmune activation. 3 In the previous reports, CIDP associated with IFN-a occurred in patients with HCV infection, 1,4-7 except in a few cases with malignant melanoma.…”
Section: Discussionmentioning
confidence: 91%
“…The effects of IVIg and PE treatment are usually seen early, but their effects are often short lived. Regular repeat treatment courses at intervals of between 2-12 weeks are usually needed to maintain improvement [15].…”
Section: Efficacy Of Therapeutic Agents In Cidpmentioning
confidence: 99%